Catechin and epicatechin reduce mitochondrial dysfunction and oxidative stress induced by amiodarone in human lung fibroblasts - Luciana Fernandes Silva Santos; Adriana Stolfo; Caroline Calloni; Mirian Salvador (Journal of Arrhythmia, 2017)
Background: Amiodarone (AMD) and its metabolite N-desethylamiodarone can cause some adverse effects, which include pulmonary toxicity. Some studies suggest that mitochondrial dysfunction and oxidative stress may play a role in these adverse effects. Catechin and epicatechin are recognized as important phenolic compounds with the ability to decrease oxidative stress. Therefore, the aim of this study was to evaluate the potential of catechin and epicatechin to modulate mitochondrial dysfunction and oxidative damage caused by AMD in human lung fibroblast cells (MRC-5). Methods: Mitochondrial dysfunction was assessed through the activity of mitochondrial complex I and ATP biosynthesis. Cell viability was evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Superoxide dismutase and catalase activity were measured spectrophotometrically at 480 and 240 nm, respectively. Lipid and protein oxidative levels were determined by thiobarbituric reactive substances and protein carbonyl assays, respectively. Nitric oxide (NO) levels were evaluated using the Griess reaction method. Results: AMD was able to inhibit the activity of mitochondrial complex I and ATP biosynthesis in MRC-5 cells. Lipid and protein oxidative markers increased along with cell death, while superoxide dismutase and catalase activities and NO production decreased with AMD treatment. Both catechin and epicatechin circumvented mitochondrial dysfunction, thereby restoring the activity of mitochondrial complex I and ATP biosynthesis. Furthermore, the phenolic compounds were able to restore the imbalance in superoxide dismutase and catalase activities as well as the decrease in NO levels induced by AMD. Protein and lipid oxidative damage and cell death were reduced by catechin and epicatechin in AMD-treated cells. Conclusions: Catechin and epicatechin reduced mitochondrial dysfunction and oxidative stress caused by AMD in MRC-5 cells.